Kebijakan manajemen preservasi naskah Minangkabau di Museum Adityawarman sebagai upaya pelestarian budaya - Astrina, Annisya Disa; Khadijah, Ute Lies Siti; Rizal, Edwin (Jurnal Informatio, 2024)
The issue of preservation can be addressed through effective preservation management. A critical component of preservation management is the establishment of preservation policies. This study aims to investigate the policies governing the preservation of Minangkabau manuscripts at the Adityawarman Museum as an effort to sustain cultural heritage. The research employs a qualitative case study methodology, utilizing data collection techniques such as observation, interviews, and literature review. The subjects of the study comprise two categories: primary and secondary subjects. Data analysis is conducted using Miles' data analysis framework, which includes data reduction, data presentation, and conclusion drawing. The findings indicate that the Adityawarman Museum's preservation policies are guided by applicable laws, technical guidelines from the National Museum, and the experiences of museum conservators. Regarding acquisition policies, the museum adheres to legal regulations concerning the procurement of goods and services. Policies on security and storage spaces are based on technical guidelines issued by the Ministry of Culture in 2001. Furthermore, environmental control in storage areas considers factors such as cleanliness, room temperature, and humidity levels. Policies regarding the lending of manuscripts involve the creation of official records witnessed by relevant parties. The management policies for the preservation of Minangkabau manuscripts reflect the museum's commitment to cultural preservation through cultural experiences and knowledge dissemination. Although the preservation management policies at the Adityawarman Museum have not been fully implemented, efforts to maintain cultural heritage continue.